2017
DOI: 10.3389/fmicb.2017.02216
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Activated Protein Kinase CgMK1 Governs Appressorium Formation, Melanin Synthesis, and Plant Infection of Colletotrichum gloeosporioides

Abstract: The fungus Colletotrichum gloeosporiodes infects plant hosts with a specialized cell called an appressorium, which is melanized and required for plant cell wall penetration. Here, we show that the mitogen-activated protein kinase CgMK1 governs appressorium formation and virulence in the poplar anthracnose fungus C. gloeosporioides. Deletion of CgMK1 impairs aerial hyphal growth and biomass accumulation, and CgMK1 is responsible for the expression of melanin biosynthesis-associated genes. CgMK1 deletion mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Fungal mitogen-activated protein kinase (MAPK) cascades play key roles in determining fungal development and responses to a variety of stress stimuli [ 1 ]. Several distinct MAPK kinase cascades exist in Saccharomyces cerevisiae , which regulate mating (Fus3/Kss1), response to high osmotic stresses (Hog1) and maintenance of cell wall integrity (CWI) (Slt2) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fungal mitogen-activated protein kinase (MAPK) cascades play key roles in determining fungal development and responses to a variety of stress stimuli [ 1 ]. Several distinct MAPK kinase cascades exist in Saccharomyces cerevisiae , which regulate mating (Fus3/Kss1), response to high osmotic stresses (Hog1) and maintenance of cell wall integrity (CWI) (Slt2) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 He et al . 23 HSPsInvolved in several common biological activities, such as transcription, translation, protein folding, and aggregation and disaggregation of proteins.Involved in stress response.Different families of HSP are expressed depending on stress type, e . g .…”
Section: Discussionmentioning
confidence: 99%
“…The antimelanin MAb 8D6 has proved very useful in the examination of melanin synthesis in C. gloeosporioides. Recently, a study by He et al [45] has demonstrated that the deletion of mitogen-activated protein kinase (MK1) in C. gloeosporioides not only impaired aerial hyphal growth and biomass accumulation but also strongly suppressed the expression of melanin biosynthesis genes, effecting a loss in the capacity for penetration and infectious growth inside the plant. Similar to other human pathogenic fungi, melanin may play a role in the determination of virulence in C. gloeosporioides.…”
Section: Discussionmentioning
confidence: 99%